A problemática da abordagem das doenças sexualmente transmissíveis pelos professores de Ciências/Biologia de escolas públicas: uma realidade de Sorocaba - Silva, Amanda de Oliveira (2013)
We sought to in this study reveal how the approach is performed on sexually transmitted diseases (STD) in state schools in the Sorocaba region with the highest rate of STDs; pinpoint the challenges and possibilities of this approach by the teacher of Science / Biology these institutions and get along with the teachers of these schools, alternative approaches significantly. It was the study of qualitative profile that had the cooperation of 9 faculty of Science / Biology, 2 coordinators of these schools of Sorocaba (SP) and coordinator of the Family Health Unit of the district in which the research took place. Through individual interviews, semi-structured, recorded, transcribed and analyzed, the results showed that teachers need better preparation to act in this theme, and that lack of stimulation directly influences the search for better results. It was also observed that it is essential the team's involvement in the theme of Health, through working with teachers for such changes to occur in the current scenario of STDs with this population of young people, and that despite the fact that this need not occur as should, however, with the research was possible to discern such involvement